Implementasi Algoritma C4.5 dan Simple Additive Weight Untuk Menentukan KPI Karyawan - Kusumaningtyas, Grasiella Yustika Rezka Talita; Wahyuddin, Mohammad Iwan (Building of Informatics, Technology and Science (BITS), 2022)
PT Kreatif Dinamika is the one of Microsoft's partner company that provides industrial solutions that consist of ERP and CRM, Power BI, Office 365 mobile applications and custom solutions. Every year conducts employee performance evaluation for employee who have worked at least one year to get an increase sallary. The primary idea of the Simple Additive Weighting technique is to get the full weighted value of every worker's overall performance on all of the attributes of the evaluation component. The C4.5 is an algorithm that used to create a decision tree. Decision tree is the structure division method and a famous predictions. In addition, after deretmine of weighted value of every attribute, SAW can select the good opportunity for classifications process from many alternatives. There are five standards that used for evaluation, there are Delivery On Time, Delivery on budget, Team Satisfaction, Soft Skill and Project Handled. The application of C4.5 algorithm on information explore in large amount include changed it into decision tree which could represent terms well. In the C4.5 algorithm, the choice of attributes as an evaluation could be very influential in acquiring an accuracy value cost primarily based totally at the outcomes of the ranking